2022
DOI: 10.1007/s10342-022-01504-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term response of open-habitats species to wildfire salvage logging: the endangered European wild rabbit as example

Abstract: Salvage logging treatments, a type of logging to economic returns after natural disturbance, are often applied in the aftermath of wildfires. Specialist or dependent species of open-habitat usually increase their populations in the short-term after wildfires and post-fire salvage logging. However, the long-term effects on threatened open-habitat species such as the European wild rabbit (Oryctolagus cuniculus L.) are still poorly known. Thus, plant productivity, habitat heterogeneity and rabbit abundance were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…However, large post-fire salvage logging operations risk the homogenization of forest ecosystems and the stability of wildlife populations on a landscape scale. In the specific case studied here, it seems evident that generating a heterogeneous landscape, through unlogged burned patches and patches logged through different management strategies, can be an appropriate strategy to improve habitat suitability and to increase the biodiversity of small mammals and other key open-land species (such as rabbits [31] or birds [38]) in the entire burned area. Indeed, wildfires (either natural or prescribed) could be the only way to fight against the process of land abandonment and rewilding at large spatial scales, reversing the decline in habitat suitability for open-land species due to habitat loss by the natural afforestation process and the subsequent recovery of small mammal predators [24,75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, large post-fire salvage logging operations risk the homogenization of forest ecosystems and the stability of wildlife populations on a landscape scale. In the specific case studied here, it seems evident that generating a heterogeneous landscape, through unlogged burned patches and patches logged through different management strategies, can be an appropriate strategy to improve habitat suitability and to increase the biodiversity of small mammals and other key open-land species (such as rabbits [31] or birds [38]) in the entire burned area. Indeed, wildfires (either natural or prescribed) could be the only way to fight against the process of land abandonment and rewilding at large spatial scales, reversing the decline in habitat suitability for open-land species due to habitat loss by the natural afforestation process and the subsequent recovery of small mammal predators [24,75].…”
Section: Discussionmentioning
confidence: 99%
“…Post-fire pl In August 2003, 4543 ha of the eastern part of this park (10% of its total surface area, Figure 1) and neighboring areas were burned by a wildfire, which affected an area dominated by pine forest, with a holm oak understory (Figure 2). Soon after the fire and within two years, most of the burned area had been completely logged using different treatments [31,37]. Here, we selected three different post-fire treatments (PFT) and a control (unburned): (a) unburned; area outside of the 2003-burned area; (b) non-managed; burned with no post-fire treatment or removal; (c) managed 1: trunk removal with branches spread over the ground (PFT1); (d) managed 2: trunk removal with branches in piles (PFT2); unburned sampled treatment was on pine forest that covers peripheral areas of the park to avoid the effect of forest type on small mammal assemblages.…”
Section: Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have previously suggested that mosaic burning will benefit biodiversity conservation as it provides a variety of resources for species dependent on different fire-age classes. Fire may generate open areas that can benefit populations of endangered species (Prodon 1994, Brotons et al 2008, Puig-Gironès et al 2022b. This is appropriate for our threatened and endemic snail species, which increase immediately after fire but practically disappear as plant succession progresses.…”
Section: Implications For Conservation and Conclusionmentioning
confidence: 99%
“…If prescribed burning is used, the time window for burning should be determined. Some authors propose burning 5 or 6 years after a wildfire to manage habitats for openhabitat species (Jacquet & Prodon 2009, Puig-Gironès et al 2022b). At a regional scale, the fire history and floristic composition will determine the recovery of each vegetation layer after fire.…”
Section: Implications For Conservation and Conclusionmentioning
confidence: 99%